The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ndt.s273287
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolic Risk Factors and Cardiovascular Safety in Ketamine Use for Treatment Resistant Depression</p>

Abstract: Introduction Ketamine exhibits antidepressant properties in treatment-resistant depression (TRD) with some concern over its cardiovascular safety and tolerability issues. This paper reports on the cardiovascular safety in short-term intravenous ketamine treatment in TRD inpatients with major depressive disorder (MDD) and bipolar disorder (BP). Materials and Methods The observational study population comprises 35 MDD and 14 BP subjects treated with intravenous ketamine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The sample selection methods for this study have been described in detail elsewhere. 9 , 10 Briefly, the patient sample comprised subjects enrolled in a naturalistic observational safety and efficacy registry protocol for ketamine infusions in TRD. Inpatients diagnosed with TRD-MDD and TRD-BP were included.…”
Section: Methods and Populationmentioning
confidence: 99%
“…The sample selection methods for this study have been described in detail elsewhere. 9 , 10 Briefly, the patient sample comprised subjects enrolled in a naturalistic observational safety and efficacy registry protocol for ketamine infusions in TRD. Inpatients diagnosed with TRD-MDD and TRD-BP were included.…”
Section: Methods and Populationmentioning
confidence: 99%
“…The study had three phases: with a single infusion, succeeded by six infusions thrice weekly over 2 weeks, and the maintenance phase with four once-weekly infusions. Bryant et al (20) reported a series of six geriatric patients treated with acute (5-27) ketamine infusions followed by the long-term maintenance phase (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Five of six patients showed a robust response including further improvement after the acute phase, but they lost the response over time.…”
Section: Discussionmentioning
confidence: 99%
“…The study population selection has been described in detail elsewhere [8,9]. Briefly, the study population comprises subjects enrolled in a naturalistic observational safety and efficacy registry protocol for ketamine infusions in TRD.…”
Section: Methods and Populationmentioning
confidence: 99%
“…The study design was discussed in detail elsewhere [8,9]. Briefly, the study followed an observational design with patients continuing baseline standard-of-care medication receiving eight ketamine infusions over 4 weeks.…”
Section: Study Design: Ketamine Infusionsmentioning
confidence: 99%